2016
DOI: 10.1167/iovs.15-18526
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Endogenous Anti(lymph)angiogenic Factors in the Aqueous Humor

Abstract: Citation: Bock F, Onderka J, Braun G, et al. Identification of novel endogenous anti(lymph)angiogenic factors in the aqueous humor. Invest Ophthalmol Vis Sci. 2016;57:6554-6560. DOI: 10.1167/iovs.15-18526 PURPOSE. The avascular cornea is in direct contact with aqueous humor (AqH). Here we investigate whether AqH exerts anti(lymph)angiogenic effects and thereby may contribute to corneal (lymph)angiogenic privilege.METHODS. Using the murine model of suture-induced inflammatory corneal hem-and lymphangiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…They may also extend into the cornea when neovascularization of the cornea develops (223). No lymphatics are located within the globe of the eye, which may be due to the presence of anti-angiogenic factors present in the aqueous humor like vasoactive intestinal peptide and α-melanocyte stimulating hormone (103). Lymphatics only contact the globe at the limbus, following the pattern of the limbal loop blood vessels.…”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%
“…They may also extend into the cornea when neovascularization of the cornea develops (223). No lymphatics are located within the globe of the eye, which may be due to the presence of anti-angiogenic factors present in the aqueous humor like vasoactive intestinal peptide and α-melanocyte stimulating hormone (103). Lymphatics only contact the globe at the limbus, following the pattern of the limbal loop blood vessels.…”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%
“…The first series of experiments evidenced that while in primary cultures of human melanocytes the αMSH acted as a mitogenic agent [ 1 , 3 ], in Mel 13 human melanoma cell line and in the B16-F10 murine melanoma cell line, this hormone did not exert the same effect. In the case of melanocyte cultures, the hyper-proliferation in response to αMSH stimulus can be found in literature [ 1 , 3 , 15 17 ]. This kind of response contravenes one of the axioms of cell biology, which associates the differentiation process with a decrease in proliferation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Only sporadic and very old studies have dealt with the capacity of activated MC1R to modulate proliferation in melanoma cells and melanocytes: transformed cells respond to αMSH by proliferating or down-regulating proliferation, according to the degree of pigmentation and the progression of the pathology [ 13 , 14 ]; primary cultures of human melanocytes respond to αMSH with a hyper-proliferative behaviour [ 1 , 3 , 15 17 ] and some authors have defined αMSH as a mitogenic agent for melanocytes [ 1 , 3 ]. The mechanism promoting hyper-proliferation in melanocytes could be recognized in the cAMP/PKA pathway itself (the canonical pathway triggered by the activation of MC1R).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it also contains several immunomodulatory factors. Just recently, we have shown that the aqueous humor exerts anti-hem-and anti-lymphangiogenic effects in vivo and in vitro [96]. Thereby, we have demonstrated that the immunomodulatory factors α-melanocyte-stimulating hormone (α-MSH) and vasoactive intestinal peptide (VIP) contained in the aqueous humor partially mediate the anti-lymphangiogenic effect [96].…”
Section: Proteins and Peptides In Lymphangiogenesismentioning
confidence: 99%